Complementary Metal‐Oxide Semiconductor and Memristive Hardware for Neuromorphic Computing. (20th May 2020) - Rahimi Azghadi, Mostafa; Chen, Ying-Chen; Eshraghian, Jason K.; Chen, Jia; Lin, Chih-Yang; Amirsoleimani, Amirali; Mehonic, Adnan; Kenyon, Anthony J.; Fowler, Burt; Lee, Jack C.; Chang, Yao-Feng
Abstract : Neuromorphic Computing In article number 1900189, Mostafa Rahimi Azghadi, Yao‐Feng Chang, and co‐workers discuss challenges and opportunities and shed light on recent advances in CMOS, SiO x ‐based memristive, and mixed CMOS‐memristive hardware for neuromorphic systems. New and published results are provided from various devices that are developed to replicate selected functions of neurons, synapses, and simple spiking networks, which are used for MNIST and pattern classification.